2021
DOI: 10.20944/preprints202101.0138.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improving Extracorporeal Shock Wave Therapy With 904 or 905 NM Pulsed, High Power Laser Pretreatment

Abstract: Extracorporeal shock wave therapy (ESWT) is a well investigated and widely used treatment modality for a number of musculoskeletal disorders. A limitation of ESWT is its potential painfulness at higher, clinically relevant energy flux density (EFD), which may limit its applicability and, thus, effectiveness. Various studies in the literature demonstrated that neither application of a higher number of extracorporeal shock waves with lower EFD nor use of local anesthesia may solve this problem. Based on the resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
(42 reference statements)
0
9
0
Order By: Relevance
“…There is increasing interest in the application of near-infrared (NIR) light for the treatment of various musculoskeletal disorders, where the NIR light is used to reduce pain and inflammation and to stimulate tissue healing [ 1 , 2 , 3 , 4 , 5 ]. A number of studies showed that high power laser therapy alone can effectively be applied to treat various musculoskeletal disorders (for examples and references, see [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing interest in the application of near-infrared (NIR) light for the treatment of various musculoskeletal disorders, where the NIR light is used to reduce pain and inflammation and to stimulate tissue healing [ 1 , 2 , 3 , 4 , 5 ]. A number of studies showed that high power laser therapy alone can effectively be applied to treat various musculoskeletal disorders (for examples and references, see [ 6 ]).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential application of NIR laser light in medicine is the augmentation of extracorporeal shock wave therapy (ESWT) [ 6 ]. ESWT is a non-pharmacological and non-surgical treatment modality for a variety of musculoskeletal disorders [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another potential application of NIR laser light in medicine is the augmentation of extracorporeal shock wave therapy (ESWT) [6]. ESWT is a non-pharmacological and nonsurgical treatment modality for a variety of musculoskeletal disorders [12].…”
Section: Introductionmentioning
confidence: 99%
“…As long as the aforementioned local self-healing power of the body is sufficient to restore physiological body structures and functions in the event of trauma or disease, all treatment efforts should primarily focus on this. A variety of methods, including but not limited to physiotherapy, osteopathy, extracorporeal shock wave therapy (ESWT) [7], laser therapy [8] and the injection of platelet-rich plasma (PRP) [9], can make valuable contributions through stimulation of local regeneration.…”
mentioning
confidence: 99%